c-Maf-positive spinal cord neurons are critical elements of a dorsal horn circuit for mechanical hypersensitivity in neuropathy - Noémie Frezel; Matteo Ranucci; Edmund Foster; Hagen Wende; Pawel Pelczar; Raquel Mendes; Robert P. Ganley; Karolina Werynska; Simon d’Aquin; Camilla Beccarini; Carmen Birchmeier; Hanns Ulrich Zeilhofer; et al. (Cell Reports, 2023)
Summary: Corticospinal tract (CST) neurons innervate the deep spinal dorsal horn to sustain chronic neuropathic pain. The majority of neurons targeted by the CST are interneurons expressing the transcription factor c-Maf. Here, we used intersectional genetics to decipher the function of these neurons in dorsal horn sensory circuits. We find that excitatory c-Maf (c-MafEX) neurons receive sensory input mainly from myelinated fibers and target deep dorsal horn parabrachial projection neurons and superficial dorsal horn neurons, thereby connecting non-nociceptive input to nociceptive output structures. Silencing c-MafEX neurons has little effect in healthy mice but alleviates mechanical hypersensitivity in neuropathic mice. c-MafEX neurons also receive input from inhibitory c-Maf and parvalbumin neurons, and compromising inhibition by these neurons caused mechanical hypersensitivity and spontaneous aversive behaviors reminiscent of c-MafEX neuron activation. Our study identifies c-MafEX neurons as normally silent second-order nociceptors that become engaged in pathological pain signaling upon loss of inhibitory control.